Correlating atomic-scale structural and compositional details of Ca-doped LaCO3 perovskite nanoparticles with activity and stability towards the oxygen evolution reaction - Bai, Fan; Schulwitz, Jonas; Priamushko, Tatiana; Hagemann, Ulrich; Kostka, Aleksander; Heidelmann, Markus; Cherevko, Serhiy; Muhler, Martin; Li, Tong (Journal of Catalysis, 2024)
Developing efficient oxygen evolution reaction (OER) electrocatalysts requires a thorough understanding of structure–activity-stability relationships, ideally at the atomic scale. Herein, we employed atom probe tomography and transmission electron microscopy to reveal compositional and structural changes on LaCoO3 and Ca-doped LaCoO3 surfaces during OER. We reveal that the topmost surfaces of pristine perovskite are terminated by the A-site element (La). After OER, amorphous La(OH)3 is formed on the surfaces of LaCoO3, which leads to significant activity deterioration. For Ca-doped LaCoO3, enhanced intercalation and penetration of hydroxide ions, along with the appearance of Co3+/4+ redox couple, are observed, contributing to its enhanced OER activity and stability. Our study demonstrates how atomic-scale compositional and structural details of electrocatalyst surfaces deepen our understanding of their activity and stability.
CRIS-Team Scopus Importer:2024-08-16
Keywords: Atom probe tomography; Ca-doped LaCoO; Oxygen evolution reaction; Perovskite electrocatalyst; Water electrolysis